Deciphering the mechanism of jujube vinegar on hyperlipoidemia through gut microbiome based on 16S rRNA, BugBase analysis, and the stamp analysis of KEEG - Duan, Guofeng; Li, Lijuan (Frontiers in Nutrition, 2023)
Background: Growing data indicates that the gut microbiome may contribute to the rising incidence of hyperlipoidemia. Jujube vinegar is said to be able to lower lipids, protect the liver, and reduce oxidant capacity, however, it is unknown whether this is due to the gut flora. To further research the role of the gut microbiome in treating hyperlipidemia with jujube vinegar, we looked into whether the action of jujube vinegar is related to the regulation of the gut microbiome. Method: Thirty male ICR mice were randomly separated into three groups and fed continuously for eight weeks: the control group, the high-fat diet (HFD) group, and the vinegar group. In each group, we measured changes in body weight, liver index, blood lipid levels, and antioxidant activity. We also analyzed mouse feces using high throughput 16srRNA sequencing to examine the relationship between jujube vinegar's hypolipidemic effect and antioxidant activity and how it affects the gut microbiome. Results: The findings demonstrated that jujube vinegar reduces body weight by 19.92%, significantly decrease serum TC (P<0.01), TG (P<0.01), LDL-C (P<0.05), AST (P<0.01), and ALT (P<0.01), and increase antioxidant performance (P<0.05) in high-fat diet-induced mice. The analysis of the gut microbiome revealed that the proportion of mice in the vinegar group was significantly higher than that in the HFD group in terms of F/B (Firmicutes/Bacteroidota) (P<0.05). That proportion was significantly inversely correlated with TC, TG, and LDL-C and positively correlated with HDL-C. Lactobacillus, and Alistipes were the biomarker genus in the vinegar group. Jujube vinegar strongly upregulated the Aerobic, Contains Mobile Elements, Facultative Aerobic, and downregulated Potential pathogens according to BugBase study (P<0.01). According to KEGG analysis, jujube vinegar was predominantly reflected in the biological process of gene function and related to signal transduction pathways, including glucagon signaling system, HIF-1 signaling pathway, adipocytokine signaling pathway, amino sugar, and nucleotide sugar metabolism, etc. Conclusion: Based on these findings, jujube vinegar may reduce hyperlipoidemia by controlling the gut microbiome and enhancing antioxidant capacity.